Research status and progress in structure and function of protein phosphatase 2C in plants - CHEN Yunrui; MAO Zhijun; LI Zhaowei; FAN Kai (浙江大学学报. 农业与生命科学版, 2021)
Protein phosphatase is one of the two key enzymes in the process of protein reversible phosphorylation. Protein phosphatase 2Cs (PP2Cs) are the important members of protein phosphatases. They are attributed to serine/threonine protein phosphatases (STPs) and can regulate the life activities of eukaryotic cells. PP2C members play an important role in hormone signal transduction pathways, especially abscisic acid (ABA) signal pathways; they can respond to various biotic and abiotic stresses, and also regulate organ development and seed germination. Recently, more and more PP2C members are found in plants. The regulation mechanisms of the PP2C members are diverse in different plants, different growth environments, and different physiological activities. The related research is an important topic. This review mainly introduces the structural characteristics, and subcellular localization of PP2C family in plants, and the research progresses in plant growth and development, hormone signal transductions, and stress responses, as well as in aspects of improving plant biological yield and promoting fruit development.